Rancang Bangun Website Sistem Informasi Inventory Barang Pada PT Oni Utama Sukses - Harfizar Harfizar; Ricky Dwi Prasetyo; Maya Indah Sari (IJAcc, 2022)
PT Oni Utama Suskes is a company engaged in electrical mechanical contractors, bridge construction, village roads, clean water assistance to produce onipanel, onilite, onitray. Problems that often occur in systems that are running are processing incoming goods data, outgoing goods data, and making stock reports only recorded on a piece of paper then copied back using Microsoft Excel software then printed and submitted to the company leadership, so that sometimes they experience problems and difficulties. in calculating goods and the information provided sometimes does not match the availability of existing goods, and the data is not integrated into a system so that the company's performance is slow. From the problems encountered, the researchers used the UML (unified modeling language) method which describes the inventory system that runs at PT Oni Utama Sukses, so a web prototype for incoming goods, outgoing goods and inventory reports was made to computerized and integrated warehousing activities. to accelerate company performance. especially in warehousing. Based on the description above, this report analyzes the inventory of goods to make it easier to obtain and issue information that will provide a better inventory system for PT Oni Utama Sukses